Selection of Covalent Organic Framework Pore Functionalities for Differential Adsorption of Microcystin Toxin Analogues - Fernandes, Soraia P S; Kovář, Petr; Pšenička, Milan; Silva, Artur M S; Salonen, Laura M; Espiña, Begoña (ACS applied materials & interfaces, 2021)
Microcystins (MCs), produced by Microcystis sp, are the most commonly detected cyanotoxins in freshwater, and due to their toxicity, worldwide distribution, and persistence in water, an improvement in the monitoring programs for their early detection and removal from water is necessary. To this end, we investigate the performance of three covalent organic frameworks (COFs), TpBD-(CF3)2, TpBD-(NO2)2, and TpBD-(NH2)2, for the adsorption of the most common and/or toxic MC derivatives, MC-LR, MC-RR, MC-LA, and MC-YR, from water. While MC-LR and MC-YR can be efficiently adsorbed using all three COF derivatives, high adsorption efficiencies were found for the most lipophilic toxin, MC-LA, with TpBD-(NH2)2, and the most hydrophilic one, MC-RR, with TpBD-(NO2). Theoretical calculations revealed that MC-LA and MC-RR have a tendency to be located mainly on the COF surface, interacting through hydrogen bonds with the amino and nitro functional groups of TpBD-(NH2)2 and TpBD-(NO2)2, respectively. TpBD-(NO2)2 outperforms the adsorbent materials reported for the capture of MC-RR, resulting in an increase in the maximum adsorption capacity by one order of magnitude. TpBD-(NH2)2 is reported as the first efficient adsorbent material for the capture of MC-LA. Large differences in desorption efficiencies were observed for the MCs with different COFs, highlighting the importance of COF-adsorbate interactions in the material recovery. Herein we show that efficient capture of these toxins from water can be achieved through the proper selection of the COF material. More importantly, this study demonstrates that by careful choice of COF functionalities, specific compounds can be targeted or excluded from a group of analogues, providing insight into the design of more efficient and selective adsorbent materials.
Keywords: mikrocystiny; chemické látky znečišťující vodu; Water Pollutants, Chemical; Metal-Organic Frameworks; Adsorption; microcystin-YR; covalent organic frameworks; čištění vody; Microcystins; microcystin-LR; Models, Molecular; adsorption; microcystin-RR; Water Purification; Microcystis; molekulární modely; microcystin-LA; toxins; porézní koordinační polymery; adsorpce